Assessment of skeletal age on the basis of DXA-derived hand scans in elite youth soccer - Romann, M.; Fuchslocher, J. (Research in Sports Medicine, 2016)
Physical performance is highly dependent on maturity. Therefore, consideration of maturity is recommended in the talent identification process. To date, skeletal age (SA) is assessed using X-ray scans. However, X-rays are associated with a 10-fold higher radiation compared to dual-energy X-ray absorptiometry (DXA). The aim of the study was to validate SA assessments in male soccer players with the DXA technique. Paired X-ray and DXA scans of the left hand of 63 Swiss U-15 national soccer players were performed. SA assessments were performed twice by two blinded raters using Tanner and Whitehouse` reference technique. Intrarater and interrater reliability as well as agreement between both techniques were tested. Intrarater and interrater reliabilities were excellent. Bland-Altman plots showed that SA assessments between X-ray and DXA differed by -0.2 years and 95% limits of agreement were ±0.6 years. Therefore, DXA offered a replicable method for assessing SA and maturity in youth soccer players.